Asymmetries and interdependencies in time use between Italian parents - Anna Laura Mancini; Silvia Pasqua (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
In recent decades, changes in parents' attitudes towards the importance of spending time with children to optimise their future behaviour and cognitive development have greatly affected patterns of time allocation among both working and non-working parents in all developed countries. We compare the two waves of the Italian Time Use dataset (1988 and 2002) to analyze how family time allocation changed over time in a country that was undergoing a marked increase in female employment rate and a continuous decline in total fertility rate. We focus especially on how parents' time with their children depends on their employment status and household characteristics. Using a simultaneous sequential approach, we consider links among the different time uses of individuals and correlations with spouses' decisions. We find that wives' time at work time strongly influences the time spent by both spouses with their children in 2002, but not in 1988. Fathers were much more involved in childcare and rearing in 2002 than in 1988. In general, as women's work time increased, substitutes for their childcare time were found within the household (fathers or other co-resident adults).
urn:nbn:de:bsz:180-madoc-31166
Keywords: D1; J13; J22; 330; Time use; parents; children